Uma proposta de sequência didática para o ensino de Programação Linear no Ensino Médio - Righetto, Luzia Francisca Pedrazzi [UNESP] (2015)
This work presents a proposal for learning education for linear programming problems and its geometric solution for the case of two variables, through a teaching sequence with problem solving, specifically for the third year of high school. It refers to a didactic sequence in which the problems will adding the degree of difficulty. We present a brief review of Analytic Geometry, linear inequalities and through simple language, how to model and solve linear programming problems that are present in our daily lives. As already appears in the Student Notebook, provided by the Department of Education of the State of São Paulo, we propose the use of didactic sequence in the classroom through the use of problem-solving methodology, where the student must reach the mathematical concept through of their own discoveries. We apply in the classroom a pretest to assess the content of our proposal in order to verify the need to redo or add some problems and we found that one of the main difficulties of the students are in the mathematical modeling of Linear Programming Problem. This difficulty is clearly related to the difficulty in interpreting text, a fact that clearly occurs by little learning through reading habit. We intend with this work to give our contribution to a better learning in linear programming problems